Where Do We Belong: Rwanda or Uganda? The Conceptualization of “Home” by the Rwandan Refugees in Uganda - Cleophas Karooma (Journal of Modern Education Review, ISSN 2155-7993, USA, 2017)
This article focuses on the conceptualization of “home” by the post-genocide Rwandan refugees in Uganda. Since 2002, the governments of Uganda, Rwanda and UNHCR have been actively promoting the repatriation of the Rwandan refugees. Despite attempts to return Rwandan refugees to their “homeland”, considerable numbers are reluctant to return and yet voluntary repatriation has been flagged as the only primary durable solution available for them in Uganda. Although the question of “home” has been studied by different scholars, little attention has been paid to the conceptualization of “home” when refugees are in a protracted situation and are unwilling torepatriate like the case of Rwandan refugees in Uganda. After two decades of exile, the Rwandan refugees have lost interest in returning home and the concept of “home” has been transformed to mean the country of asylum-Uganda where they have peace. Therefore, this article disagrees with the notion that “repatriation equals home coming model”. The argument is that home and the country of origin do not have to be the same.
Keywords: Rwanda; Uganda; “home”; Rwandan refugees; durable solutions; repatriation; protractedness